A selection guide for efficient graphene oxide-composite adsorbents - Jafar I. Abdelghani; Fawwaz I. Khalili; Nabil N. AL-Hashimi; Amjad H. El-Sheikh; Moayad A. Khwara (Water Cycle)
Many adsorbents for various pollutants are now being developed, especially after the great developments in the nanotechnology. Therefore, there is an urgent need to develop a guide for selecting the most appropriate adsorbent from a practical standpoint. In fact, relying on the magnitude of adsorption capacity alone is not sufficient to decide the usability of an adsorbent in real applications. Based on this, a selection guide has been proposed to choose the most appropriate adsorbent based not only on the adsorption capacity but also on the other factors related to the batch process. This guide was proposed based on the exceptional performance of graphene oxide and graphene oxide composites (Qmax >1000 mg/g) to sequestrate textile dyes, as evidenced by the recent literature. To create the guide, 74 graphene oxide-based adsorbents with high retention for 36 dyes of different classes were examined. The collected GO-adsorbents were classed into four groups according to the added substrates. From the experimental results, the guide's criteria for selecting the most practical adsorbent were set as follows: adsorption capacity ≥684 mg/g, solid to liquid ratio ≤0.9 g/L, equilibrium time ≤70 min, pH 10.0 for cationic dyes and 5.5 for anionic dyes, recyclability ≥5 cycles with a final efficiency ≥90 %, and ease recovery from solution by an external magnet or decantation. Based on the guide, the winner GO-adsorbents were tetrazolyl-octadecylamine-GO, polyethylenimine-polyvinyl alcohol-GO, and Fe3O4-triethylenetetramine-β-cyclodextrin-GO as they fulfill most of suggested criteria. Although the proposed guide was created for graphene oxide-dye system, similar guides for other systems would be created following the outlined strategy.